Construction Claims Management in United Arab Emirates Construction Industry - Shadid, Mosab Sael Rushdi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The United Arab Emirates (UAE) have developed rapidly during the last two decades expanding in an astonishing and unbelievable manner. This development is seen through the increase of the production in construction industry over the years. One of the most negative constraint faced by the construction industry are the claims demanding either additional payment or/and time as a consequence or condition not stated in the contract. Construction contracts followed in the UAE are either Lump Sum or Unit Rate while Lump Sum Contracts are more dominant. The contract administration in the UAE is done by the same company that designed and made all required documentations of the construction in behalf of the owner. In this study the current claim management system followed in the UAE is examined and the nature of claims, type of claims, causes and effects of claims are analyzed in depth. This is done through an analysis of two projects constructed by the same company referred to as QWE Construction Company. The case study is carried out by conducting interviews that were questioning inquiries regarding claim management system, causes and effects, procedure of claim submission, initial steps for the claim resolution and resolution method or negotiation outcomes. Moreover a questionnaire was distributed to different firms and organizations in the construction industry regarding claim management, Fédération International Des Ingénieurs-Conseils (FIDIC) contracts, role of Engineers, and record keeping and documentation systems. Some of the findings indicate that there is a high dependency on a third party for claim formulation, the minimal interference of the Engineer for resolving the claim and the lack of record keeping and documentation. The study emphasizes on minimizing the loss of rights and elaborate on the other constraints that are faced in claim management.

Öz:Birleşik Arap Emirlikleri (BAE) son yirmi yıl içinde inşaat endüstrisindeki üretimmin artışı ile birlikte hızlı bir gelişme göstermiştir. BAE’nde tercih edilen inşaat sözleşmeleri ağırlıklı olarak Götürü Bedel sözleşmeler olmakla birlikte Birim Fiyat sözleşmeleridir. Sözleşme yönetimi, projenin tasarımını yapan ve malsahibi adına inşaat ile ilgili tüm dökümantasyonu hazırlayan ayni firma tarafından yapılır. BAE’de inşaat endüstrisinin karşılaştığı en zorlu sınırlandırmalardan biri sözleşmede belirtilmemiş şartlar sebebiyle ilave ödeme ve veya zaman talep edilen durumlardır. Bu tez çalışmasında şu anda yürürlükte olan sözleşme hak iddiası yönetim sistemi konu edilmiş olup, hak iddiası doğası, çeşitleri, gerekçeleri ve etkilerini detaylı analiz edilmektedir. Bu analizler QWE inşaat firmasının inşa ettiği iki projeyi kapsamaktadır. Vaka çalışmasında yapılan mülakatlarda yöneticilere hak iddiası yönetimi, gerekçeleri ve etkileri, hak iddiası talebi prosedürü, talebin çözümü ve metodu veya görüşmelerin çıktıları sorulmuştur. Ek olarak, inşaat sektöründeki farklı şirket ve kurumlara, hak iddiası yönetimi, Uluslararası Müşavir Mühendisler Federasyonu (FIDIC) sözleşmeleri, Mühendislerin rolü, kayıt tutma ve dokümantasyon sistemleri ile ilgili bir anket dağıtılmıştır. Elde edilen bulgular hak iddiası talebi formülasyonu için üçüncü bir partiye yüksek oranda bağımlılık olduğunu, Mühendisin iddianın çözümünde minimum rol oynadığını, kayıt tutma ve dokümantasyon eksikliğini ortaya çıkarmıştır. Bu tez çalışması hak iddiası yönetiminde ilgili tarafların hak kaybına uğramasını en aza indirmenin ve diğer ilgili sınırlamalar üzerinde durulmasının önemini vurgulamaktadır.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assoc. Prof. Dr. Ibrahim Yitmen.
Keywords: Civil Engineering; Construction industry - Constraction Claims - United Arab Emirates; Construction contracts - Claims; UAE construction industry; Contract Administration; Claim management; causes and effects; FIDIC contracts